2020
DOI: 10.3892/etm.2020.8674
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the secretion of mesenchymal stem cell immunoregulatory factors by hydrolyzed fish collagen

Abstract: The aim of the present study was to investigate the possible immunomodulatory effects of osteogenically differentiated bone marrow mesenchymal stem cells induced by hydrolyzed fish collagen. Marine biomaterials have attracted significant attention for their environmental friendliness and renewability. Hydrolyzed fish collagen (HFC) has been discovered to induce the osteoblastic differentiation of stem cells, which underlies the foundation for its application in tissue engineering. Stem cells and their biomater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Therefore, understanding the effects of biomaterials on the immunoregulatory properties of MSCs is becoming an increasingly important question to address ( 80 , 81 ). Recently, Liu and Sun ( 82 ) established a direct contact co-culture model consisting of hydrolyzed fish collagen treated-bone marrow-derived MSCs and RAW264.7 macrophages. Hydrolyzed fish collagen-induced bone marrow-derived MSCs were found to inhibit the expression and secretion of IL-6 and IL-1β, whilst increasing the levels of inflammatory zone 1 (FIZZ1) and CD206 in macrophages.…”
Section: Marine Collagen and Their Immunomodulatory Properties In Mes...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, understanding the effects of biomaterials on the immunoregulatory properties of MSCs is becoming an increasingly important question to address ( 80 , 81 ). Recently, Liu and Sun ( 82 ) established a direct contact co-culture model consisting of hydrolyzed fish collagen treated-bone marrow-derived MSCs and RAW264.7 macrophages. Hydrolyzed fish collagen-induced bone marrow-derived MSCs were found to inhibit the expression and secretion of IL-6 and IL-1β, whilst increasing the levels of inflammatory zone 1 (FIZZ1) and CD206 in macrophages.…”
Section: Marine Collagen and Their Immunomodulatory Properties In Mes...mentioning
confidence: 99%
“…These observations were shown to be mediated by the prostaglandin E2/prostaglandin receptor EP4-C/CCAAT-enhancer-binding protein axis. This suggested that osteogenically differentiated MSCs treated with hydrolyzed fish collagen retained their immunomodulatory properties ( 82 ). However, only a limited number of studies, as those aforementioned, have examined the effects of biomaterials on the immunoregulatory properties of MSCs.…”
Section: Marine Collagen and Their Immunomodulatory Properties In Mes...mentioning
confidence: 99%